Answer:
Option B
Step-by-step explanation:
we know that
The volume of the cone is equal to
[tex]V_c=\frac{1}{3}B_c(h)[/tex]
where
Bc is the area of the circle of the base of the cone
The volume of the square pyramid is equal to
[tex]V_p=\frac{1}{3}B_p(h)[/tex]
where
Bp is the area of the square base of the pyramid
we know that
[tex]\frac{B_c}{B_p}=\frac{\pi}{4}[/tex]
[tex]B_c=\frac{\pi}{4}(B_p)[/tex]
substitute in the formula of volume of the cone
[tex]V_c=\frac{1}{3}B_c(h)[/tex]
[tex]V_c=\frac{1}{3}(\frac{\pi}{4}(B_p))(h)[/tex]
Remember that
[tex]V_p=\frac{1}{3}B_p(h)[/tex]
substitute
[tex]V_c=(\frac{\pi}{4})V_p[/tex] ----> StartFraction pi Over 4 EndFraction the volume of the pyramid
or
[tex]V_c=(\frac{\pi}{4})(\frac{(2r)^2h}{3})[/tex] ----> StartFraction pi Over 4 EndFraction (StartFraction (2 r) squared (h) Over 3 EndFraction)
or
[tex]V_c=\frac{1}{3}\pi r^{2} h[/tex] ----> One-thirdπr^2h